Eco's Chaosmos : From the Middle Ages to Postmodernity - Farronato, Cristina (Book collections on Project MUSE., 2003)
"While Umberto Eco's intellectual itinerary was marked by his early studies of post-Crocean aesthetics and his concentration on linguistics, information theory, structuralism, semiotics, cognitive science, and media studies, what distinguishes his critical and fictional writing is the tension between a typically medieval search for a code and a hermeneutic representative of deconstructive tendencies. This tension between cosmos and chaos, order and disorder, is reflected in the word chaosmos." "In this assessment of the philosophical basis of Eco's critical and fictional writing, Cristina Farronato explores the other distinctive aspect of Eco's thought - the struggle for a composition of opposites, the outcome deriving from his ability to elicit similar contrasts from the past and replay them in modern terms. Focusing principally on how Eco's scholarly background influenced his study of semiotics, Farronato analyses The Name of the Rose in relation to William of Ockhman's epistemology, C.S. Peirce's work on abduction, and Wittgenstein's theory of language. She also discusses Foucault's Pendulum as an explicit comment on the modern debate on interpretation through a direct reference to early modern hermetic thought, correlates The Island of the Day Before as a postmodern mixture of science and superstition, and reviews Baudolino as a historical/fantastic novel that again situates the Middle Ages in a postmodern context. Demonstrating Eco's use of semiotic theory, Eco's Chaosmos shows how critical models of the past map contemporary literature and culture."--Jacket